Pemberdayaan Kader Melalui Pelatihan Dental Health Education di Kota Banda Aceh - Rahayu, Eka Sri; Reca, Reca; Fitriani, Fitriani (Journal of Community Service and Society Empowerment, 2024)
Health cadres play a crucial role in enhancing the dental and oral health status of the community, making it essential for them to be equipped with adequate knowledge through structured education and training programs. In addition to carrying out routine tasks, cadres are also responsible for providing education on maternal and child health, necessitating their mastery of various techniques and skills. This community service project employs a descriptive method, involving 20 health cadres from posyandu and PKK, and utilizes univariate analysis for data interpretation. The intervention in the form of training aims to assist cadres in transferring knowledge to the community, particularly to high-risk groups for dental and oral diseases. The focus of this initiative is on promotive and preventive services managed by the cadres to engage the entire community. The Dental Health Education (DHE) training significantly improved the knowledge of the cadres, with 85% categorized as having poor knowledge before the training, rising to 100% in the good knowledge category afterward. It is recommended that training be conducted on an ongoing basis with follow-up sessions to ensure that cadres continuously update their knowledge and skills.